2021
DOI: 10.15388/infedu.2021.03
|View full text |Cite
|
Sign up to set email alerts
|

Use of Digital Mind Maps in Technology Education: A Pilot Study with Pre-Service Science Teachers

Abstract: This case study aims at ensuring preservice science teachers to acquire experience by creating paper-based mind maps (PB-MM) and digital mind maps (D-MM) in technology education and to reveal their opinions on these mind mapping techniques. A total of 32 preservice science teachers, enrolled in the undergraduate program of Science Teaching at a university in Turkey, participated in this study. During the first three weeks of the six-week study, participants created PB-MM for certain subjects in science educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Related ideas radiate outward from the centre, forming a radiant structure. Adapted from Morin (2018) Debagg et al (2021) conducted a pilot study with the undergraduate students majoring in science teaching at a university in Turkey using the Coggle and found that a digital map is a beneficial tool for strengthening, evaluating, and envisioning learning in general -making courses more enjoyable and providing ease of use. Furthermore, Al-Jarf (2009) described that digital mind mapping could enhance students' creative thinking, especially in generating new ideas.…”
Section: The Digital Mind Mapmentioning
confidence: 99%
“…Related ideas radiate outward from the centre, forming a radiant structure. Adapted from Morin (2018) Debagg et al (2021) conducted a pilot study with the undergraduate students majoring in science teaching at a university in Turkey using the Coggle and found that a digital map is a beneficial tool for strengthening, evaluating, and envisioning learning in general -making courses more enjoyable and providing ease of use. Furthermore, Al-Jarf (2009) described that digital mind mapping could enhance students' creative thinking, especially in generating new ideas.…”
Section: The Digital Mind Mapmentioning
confidence: 99%
“…The questions were improved in light of experts and respondents considerations. The researchers piloted a self-develop questionnaire on a small scale of the respondents that were not included in the final data collection procedures (Debbag et al, 2021). The pilot studies are the pivotal element of excellent study design (Lee & Wessol, 2021) that provide logical insight (Coates, 2021) confers warning about instrument failure/success (Smith, 2021) and research protocols (McKenney & Reeves, 2021).…”
Section: Instrumentationmentioning
confidence: 99%
“…Meanwhile, the mind-mapping technique has been proven effective for improving student learning performance in various disciplines, for example in Chemistry (Redhana et al, 2021), English vocabulary (Wang & Dostál, 2018), and science (Debbag et al, 2021). In addition to improving student learning outcomes, researchers have also reported the benefits of mind-mapping in increasing students' creativity and critical thinking skills (for example, Karim & Mustapha, 2020;Rosba et al, 2021), and motivation (Sabarun et al, 2021).…”
Section: Introductionmentioning
confidence: 99%